Balistic - Kaosayananda, Wych.; Banderas, Antonio. 1960-; Lucy Liu; Gregg Henry; Ray Park (USA Franchise Pictures, 2002)
Tasked with destroying each other, an FBI agent and a rogue NSA agent soon discover that there's a much bigger enemy at work.
Your most dangerous enemies are the friends you've double-crossed.
Alan B. McElroy
Language(s): English, Turkish
Subtitle(s): English, Turkish
Keywords: action